How religion shapes the behavior of students: a comparative analysis between Romanian confessional and non-confessional schools - Coman, Claudiu; Neagoe, Alexandru; Onaga, Florina Magdalena; Bularca, Maria Cristina; Otovescu, Dumitru; Otovescu, Maria Cristina; Talpă, Nicolae; Popa, Bogdan (Frontiers in Education, 2024)
IntroductionWhile being a complex concept, religion can shape the way people in general, and students in particular, behave and make decisions in different types of contexts. In this regard, our paper aimed to assess the way religiosity influences the school climate and the social behavior of students from confessional and non-confessional Romanian high schools in order to raise awareness regarding the importance of religion in students’ education.MethodsWe used a quantitative method and we applied a questionnaire to 353 students from confessional and non-confessional high schools in Timișoara, Romania.Results and discussionThe results of our study show positive correlations between religiosity and school climate, revealing that students from confessional schools have stronger feelings of belonging and better relationships with their teachers.